SHADOWING EFFECT GRUP TIANG AKIBAT GAYA LATERAL PADA GEDUNG IKPT - Noviati, Tati; Wulandari, Sri (Universitas Gunadarma, 2014)
In analyzing the behavior of pile groups due to lateral forces in buildings, in addition to taking into account the carrying capacity pertiang in the group must also pay attention to aspects geotekniknya that nature - the nature and behavior of the soil that received the lateral load. This study was conducted to determine the deflection and bending moment on a single pole and pole group 3, 5, and 7 when it receives a static horizontal load on the mast head wedged condition (fixed head). Location of the study was taken from the region MT.Haryono storey building, Jakarta ie IKPT Building. Research deflection and bending moment pole performed using Plaxis 3D Foundation Software V1.5. Lateral load is given once the loading of 2 different direction, namely the direction of the x and z, equal to 7 tons pertiang. Shadowing effect can be seen using Plaxis 3D Foundation program V1.5. An odd number of poles in the pole groups with different forms of pile cap, will produce different maximum deflection values ranged between 0-5% in buildings IKPT. Differences 2 x direction bending moment will be bigger than the bending moment - 3, whereas the z-direction bending moments keterbalikannya 2 z direction is smaller than the bending moment - 3. It is due to differences in the pile cap shape and direction of the assignment.Keywords: group pole, lateral force, shadowing effects, Plaxis 3D Foundation